2020
DOI: 10.5617/adno.7852
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisering i grunnskolelærerutdanningen: Om faglige forskjeller i arbeidet med profesjonsfaglig digital kompetanse

Abstract: Forskning viser at utviklingen av lærerstudenters profesjonsfaglige digital kompetanse (PfDK) i svak grad har vært arbeidet med i norsk grunnskolelærerutdanning. Imidlertid er det behov for oppdaterte studier og kunnskap om hvordan ulike fag i dag arbeider med PfDK. I artikkelen har vi lagt Rammeverk for lærerens profesjonsfaglige digitale kompetanse (lansert av Utdanningsdirektoratet i 2017) til grunn når vi har innhentet og analysert data. Vi undersøker om det er forskjell mellom hvordan lærerutdannere fra u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…There have been many attempts to create a framework that explains, defines or facilitates teacher's pedagogical digital competence, such as TPACK (Mishra and Koehler, 2006), SAMR (Puentedura, 2015), and DigCompEdu (Punie and Redecker, 2017); however, these models offer little concrete recommendations and guidelines for defining and developing teacher's professional digital competence (PDC) and can therefore be seen as quite generic (Hjukse et al, 2020). Professional Digital Competence Framework for Teachers framework, developed by Kelentrić et al (2017) for The Norwegian Centre for ICT in Education, was launched by the Norwegian Directory of Education and Training and was chosen to frame this study due to its relevance to the context and design that has targeted primary and secondary education in particular.…”
Section: Teacher's Professional Digital Competence and Classroom Mana...mentioning
confidence: 99%
“…There have been many attempts to create a framework that explains, defines or facilitates teacher's pedagogical digital competence, such as TPACK (Mishra and Koehler, 2006), SAMR (Puentedura, 2015), and DigCompEdu (Punie and Redecker, 2017); however, these models offer little concrete recommendations and guidelines for defining and developing teacher's professional digital competence (PDC) and can therefore be seen as quite generic (Hjukse et al, 2020). Professional Digital Competence Framework for Teachers framework, developed by Kelentrić et al (2017) for The Norwegian Centre for ICT in Education, was launched by the Norwegian Directory of Education and Training and was chosen to frame this study due to its relevance to the context and design that has targeted primary and secondary education in particular.…”
Section: Teacher's Professional Digital Competence and Classroom Mana...mentioning
confidence: 99%
“…Forskning på digital kompetanse i en laererutdanningskontekst inkluderer studier om hvordan laererutdanninger implementerer digital kompetanse i studiene (Amdam et al, 2022;Thorvaldsen, 2020), dokumentanalyser av ulike styringsdokumenter (Arstorp, 2021) og hvilke erfaringer laererstudenter og nyutdannede laerere har med å utvikle sin digitale kompetanse gjennom studiet (Almås et al, 2021;Gudmundsdottir & Hatlevik, 2018;Johannesen & Øgrim, 2020). Empiriske studier om laererutdanneres erfaring med, og utvikling av, digital kompetanse er imidlertid et underforsket område (Hjukse et al, 2020;Lund & Aagaard, 2020;Røkenes et al, 2022;Örtegren, 2022).…”
Section: Tidligere Forskning På Laererutdanneres Digitale Kompetanseunclassified
“…Utviklingen av laererutdanneres digitale kompetanse har vaert gjennomgående svakt forankret i laererutdanningene (Hjukse et al, 2020;Kelentrić et al, 2017;Krumsvik et al, 2012). Flere studier viser imidlertid at kollegabasert veiledning, tilgjengelig teknisk support, kritisk refleksjon, pedagogiske diskusjoner, tid på arbeidsplanen og administrativ støtte har stor betydning for om laererutdannere prioriterer å utvikle sin digitale kompetanse eller ikke (Almås, 2021;Amdam et al, 2022;Andreasen et al, 2022;Røkenes et al, 2022;Aagaard et al, 2022).…”
Section: Tidligere Forskning På Laererutdanneres Digitale Kompetanseunclassified
“…al. 2021;Hjukse et al, 2020) have indicated that the dimensions in the PDC framework are not only intertwined but also overlapping. The present model entangles the dimensions, rearranges their content, and shows their relation in layers, similar to Krumsvik's (2014) model.…”
Section: Figure 2 Teacher Educators' Digital Competencementioning
confidence: 99%